Pelatihan dan Pendampingan Abdominal Exercise, Kegel Exercise pada Remaja Putri - Gita Ayu Indria; Ajeng Sekar Arum Hanafi; Nadia Farahsyifa (Jurnal LINK, 2025)
Adolescent reproductive health, particularly among adolescent girls, continues to require considerable attention from various stakeholders. In 2021, the number of adolescent girls in Cilacap Regency reached 956,682, with 1.03%–1.24% experiencing dysmenorrhea. The occurrence of dysmenorrhea among adolescent girls is influenced by multiple factors, and the symptoms frequently disrupt their daily activities. One of the complementary therapies that can be administered to reduce dysmenorrhea is abdominal exercise and Kegel exercise. These exercises help improve blood flow to the uterus, thereby inhibiting the release of prostaglandins, as excessive prostaglandin production contributes to pain. The training and mentoring activities on abdominal and Kegel exercises were conducted from June to August 2025. The program consisted of several stages: problem identification through interviews, a socialization stage conducted via lectures and discussions, a training phase, and finally, an evaluation stage to measure the program’s effectiveness. The training and mentoring were implemented with 10 adolescent girls who are members of the Adolescent Posyandu of RW 11, North Cilacap District, Cilacap Regency. The results showed a reduction in menstrual pain intensity, with 70% of participants achieving the category of mild pain. It is expected that, following the training and mentoring provided, the participants will consistently engage in abdominal and Kegel exercises to further reduce menstrual pain.